The Efektivitas-NTU dan Koefisien Perpindahan Panas Keseluruhan Alat Penukar Panas Barisan Pipa tanpa Sirip Susunan Staggered dan Aligned Orientasi untuk Pengeringan - Murti, Made Ricki (Jurnal Energi Dan Manufaktur; Vol 16 No 1 (2023)DO - 10.24843/JEM.2023.v16.i01.p03, 2023)
This study has designed an unfinned tubular pipes heat exchanger that oriented for drying applications. Pipes bank with staggered and aligned arrangement by flowing two working fluids are the flue gas from LPG combustion and air as drying fluid. Heat exchange occurs from the flue gas of LPG as a hot fluid to the air flowing is cold fluid as heat receiver. Flue gas is produced by burning LPG in the combustion chamber and flowing through the inside of the pipes, while air flows on the outside surface of unfinned pipes. Variations are made on the mass flow rate of fuel consumption flowing into the combustion chamber and the air mass flow rate on the outer surface of pipes. Data taken are includes: air inlet and outlet temperatures at outside surface of heat exchanger pipes, flue gas inlet and outlet temperatures inside surface of heat exchanger pipes, air flow velocity, flue gas flow velocity, and mass flow rate of fuel consumption. The performance that analyzed are includes: Heat Exchanger effectiveness, NTU, and overall heat transfer coefficient. From the results can be concluded that the average of performance values on staggered pipes bank arrangement is higher than aligned pipes bank arrangement. On the variation of the mass flow rate of fuel consumption that flow at the inner surface of the rows of pipes, it produces the maximum effectiveness value of 89.18% for the staggered arrangement and 86.26% for the aligned arrangement, that occurs at the mass flow rate of 0.033gram/s, the maximum NTU value of 2.11 for the staggered arrangement and 1.99 for the aligned arrangement, that occurs at mass flow rate of 0.027gram/s, and the maximum overall heat transfer coefficient of 27.56 W/m 2 .K for the staggered arrangement and 25, 99 W/m 2 .K for the aligned arrangement, that occurs at the mass flow rate of 0.04gram/s. On variation of the air mass flow rate that flows at outer surface of the rows of pipes, the staggered arrangement produces the maximum effectiveness value of 95.4%, the maximum NTU value of 2.37, and the maximum overall heat transfer coefficient value of 28.16 W/m 2 .K and all of them occurs at the air mass flow rate of 0.028 kg/s.